2021
DOI: 10.1002/cbdv.202000800
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Preliminary Antileukemic Activity of 4‐Methoxybenzyl Derivatives Bearing Imidazo[2,1‐b][1,3,4]thiadiazole

Abstract: In this study, we synthesized 22 compounds in a series with various substitution on imidazo[2,1‐b][1,3,4]thiadiazole. The potential cytotoxic activity of these compounds investigated in leukemia cell lines by Differential Nuclear Staining (DNS). Our results identified two compounds, 2‐(4‐methoxybenzyl)‐6‐(2‐oxo‐2H‐chromen‐3‐yl)imidazo[2,1‐b][1,3,4]thiadiazol‐5‐yl thiocyanate and 6‐(4‐chlorophenyl)‐2‐(4‐methoxybenzyl)imidazo[2,1‐b][1,3,4]thiadiazole‐5‐carbaldehyde, exhibited the most cytotoxic effect against mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The XP Glide score was calculated based on the binding interaction, Van der Waals, electrostatic potential, and strain energy calculation. The binding of the ligands with HMGB1 (PDB ID: 2LY4) and HMGB1 Box A (PDB ID: 4QR9) was examined using the Schrödinger Maestro interface (Schrödinger 11.8) [21] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XP Glide score was calculated based on the binding interaction, Van der Waals, electrostatic potential, and strain energy calculation. The binding of the ligands with HMGB1 (PDB ID: 2LY4) and HMGB1 Box A (PDB ID: 4QR9) was examined using the Schrödinger Maestro interface (Schrödinger 11.8) [21] …”
Section: Methodsmentioning
confidence: 99%
“…The binding of the ligands with HMGB1 (PDB ID: 2LY4) and HMGB1 Box A (PDB ID: 4QR9) was examined using the Schrödinger Maestro interface (Schrödinger 11.8). [21]…”
Section: In Silico Molecular Docking Studiesmentioning
confidence: 99%
“…The imidazo ring [2,1-b] was fused with 2-amino-1,3,4-thiadiazole, which resulted in imidazo [2,1-b] [1,3,4]thiadiazole with antibacterial [4][5][6], antifungal [7], anti-inflammatory [8,9], anticancer [10], analgesic [11], and antitubercular properties [12,13]. We have reported imidazo [2,1-b] [1,3,4]thiadiazoles (II) as cytotoxic agent [14][15][16][17][18][19]. Recent studies have reported experiments on imidazo [2,1-b] [1,3,4] thiadiazoles (III) as non-steroidal ecdysone agonists [20].…”
Section: Introductionmentioning
confidence: 99%